2012
DOI: 10.1007/s10815-012-9761-7
|View full text |Cite
|
Sign up to set email alerts
|

Frequent polymorphisms of FSH receptor do not influence antral follicle responsiveness to follicle-stimulating hormone administration as assessed by the Follicular Output RaTe (FORT)

Abstract: Antral follicle responsiveness to FSH, as far as measured by the FORT, is not influenced by the presence of SNPs of FSHR 307Ala and 680Ser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 15 publications
5
23
1
Order By: Relevance
“…The data reported in Supplementary Table 1 show that some studies confirmed our original results (29,36,37,38,39,40) but others did not, especially those conducted in women of advanced age (41,42,43,44). Serum FSH levels were not significantly different between FSHR genotypes in older women (41,42,43,44) and in conditions of very high FSH concentrations, such as in postmenopausal women (45) and in women with premature ovarian failure (46).…”
Section: European Journal Of Endocrinologymentioning
confidence: 66%
See 1 more Smart Citation
“…The data reported in Supplementary Table 1 show that some studies confirmed our original results (29,36,37,38,39,40) but others did not, especially those conducted in women of advanced age (41,42,43,44). Serum FSH levels were not significantly different between FSHR genotypes in older women (41,42,43,44) and in conditions of very high FSH concentrations, such as in postmenopausal women (45) and in women with premature ovarian failure (46).…”
Section: European Journal Of Endocrinologymentioning
confidence: 66%
“…Serum FSH levels were not significantly different between FSHR genotypes in older women (41,42,43,44) and in conditions of very high FSH concentrations, such as in postmenopausal women (45) and in women with premature ovarian failure (46). Patient inclusion criteria are important as well, because studies excluding (young) women with basal FSH levels O10 IU/l, potentially excluding p.N680S S carriers, did not reveal any genotype-related difference (37,47,48).…”
Section: European Journal Of Endocrinologymentioning
confidence: 98%
“…A total of 1019 citations were initially retrieved with our search strategy, in which 1003 citations were carefully excluded. Only 16 studies involving 4287 patients were included in our meta-analysis [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The process of identification of the eligible studies and the reasons for exclusion were presented in Fig.…”
Section: Identification Of Studies and Quality Assessmentmentioning
confidence: 99%
“…In addition to these SNPs, splice variants in FSHR that have been identified in women undergoing ovarian stimulation may also contribute to the variability in ovarian response. However, results from multiple studies are conflicting, and previous meta-analyses have failed to confirm the association between FSHR Asn680Ser polymorphism and the outcomes related to COH [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. A pooled analysis of only four studies, as well as a recent meta-analysis, showed that the 680 SS genotype of FSHR played a role in the ovarian response during stimulation with exogenous gonadotropin [11,30].…”
mentioning
confidence: 99%
“…Furthermore, in a small study conducted with 37 patients, the A/A (Asn/Asn) variant was correlated to the severity of ovarian hyperstimulation syndrome (OHSS) [21]. In other studies, the association of the G/G variant with a poor ovarian response was not demonstrated, either for the number of oocytes retrieved [22] or for the FORT [23]. Even those patients who were homozygous for the G/G variant revealed a higher number of mature oocytes than the patients homozygous for the A/A variant [10].…”
Section: Introductionmentioning
confidence: 96%